VALUING ARTS INTEGRATION IN AGE-FRIENDLY COMMUNITIES - Lipscomb, V.B. (Innov Aging, 2017)
Two foci of the 2015 Summit on Creativity and Aging in America were Age-Friendly Community Design and Lifelong Learning and Engagement in the Arts, which includes how the arts reflect and/or reshape contemporary cultural understanding of aging (Hanna et al. 2016). This symposium examines how integrating the arts into the age-friendly model can enhance quality of life for elders as well as combat community ageism. The first paper approaches arts integration on a national level, identifying how policies on aging impact the benefits of and need for arts in age-friendly communities. Surveys of age-friendly communities show the essential role that humanities and the arts play in creating an inclusive environment. The second paper addresses a collaboration between arts professionals and age-friendly community leaders. A theatrical production on aging arose from interviews with more than 100 residents of an age-friendly community; analysis of audience talkbacks indicates that the program promoted respect and social inclusion, major issues addressed in age-friendly community design. The final presentation analyzes the process of a major collaborative arts-based research project, finding that participation in devising theatre enhances quality of life for older people. The discussant will draw on extensive experience with interdisciplinary arts-related approaches to aging research and policy. These presentations will offer insights into the creation and implementation of arts policies as key to the design of age-friendly communities.